Treatment of distal bronchial stenosis after bilateral lung transplantation - S. V. Golovinskiy; N. B. Nechaev; V. N. Poptsov; M. A. Rusakov (Вестник трансплантологии и искусственных органов)
The efﬁ ciency of lung transplantation is considerably limited by the complications associated with the bronchial pathologies. Despite the progress of the treatment methods, bronchial complications are still remaining as an actual problem in the postoperative period with frequency of occurrence from 7 to 29%. However, the bronchial stenosis are the most common bronchial complications after lung transplantation with mortality from 2 to 4%.Aim. To study an experience of our center of bronchial stenosis treatment in lung recipients. Materials and methods. 34 patients underwent lung transplantation from September 2014 to January 2017. 6 (16%) of them had a stenosis of lobar or segmental bronchi from 84 to 494 postoperative day. 5 (83%) of them have demonstrated multifocal lesions. In all of the cases there was performed an endoscopic bougienage, which involved a balloon dilatation and electrocoagulated incision of granular tissue under X-ray control. After that the patients were administrated by everolimus.Results. Restenosis was formed in 132,0 ± 94,2 postoperative day after primary treatment in all patients. In four cases (67%) we used nitinol stent placement under X-ray control. There were no complications. In 3 cases stents were dislocated distally, so we needed to use repeated endoscopic bougienage to replace the stent. Using of everolimus has allowed to decrease the rate of restenosis, but it need future research.Conclusion. Distal bronchial stenosis after lung transplantation can be managed with endoscopic bougienage and stent placement. Adding everolimus has not signiﬁ cantly affected the risk of frequency of restenosis.